2023
DOI: 10.1093/europace/euad118
|View full text |Cite
|
Sign up to set email alerts
|

Personalized pulmonary vein antrum isolation guided by left atrial wall thickness for persistent atrial fibrillation

Abstract: Aims Pulmonary vein (PV) antrum isolation proved to be effective for treating persistent atrial fibrillation (PeAF). We sought to investigate the results of a personalized approach aimed at adapting the ablation index (AI) to the local left atrial wall thickness (LAWT) in a cohort of consecutive patients with PeAF. Methods and results Consecutive patients referred for PeAF first ablation were prospectively enrolled. The LAWT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…11 They also showed similar results in persistent AF. 12 These results indicated that a high rate of AT recurrence-free survival in the CLOSE protocol was not related to the higher AI target values but to the higher rate of FPI.…”
Section: Fpi and Pvi Durabilitymentioning
confidence: 81%
“…11 They also showed similar results in persistent AF. 12 These results indicated that a high rate of AT recurrence-free survival in the CLOSE protocol was not related to the higher AI target values but to the higher rate of FPI.…”
Section: Fpi and Pvi Durabilitymentioning
confidence: 81%
“…However, wall thickness measurements do not provide a real‐time assessment of these variables, and accurately measuring the wall thickness just underneath the ablation tags is limited because of technical difficulties in incorporating such information into the 3D mapping system. Specific software that detects the wall thickness and integrates it into the CARTO mapping system could be more feasible in this regard 15 . On the other hand, the LA EGM voltage amplitude is a simple real‐time variable that can be obtained at sites accurately mapped in 3D.…”
Section: Discussionmentioning
confidence: 99%
“… 1 In all patients, an MDCT study was obtained prior to the ablation procedure; post-processing aimed for the reconstruction of MDCT-derived 3D maps with LAWT information was performed, as previously described. 14 The exclusion criteria were age <18 years, previous atrial fibrillation (AF) ablation procedure, impossibility to obtain a pre-procedural MDCT, any clinical condition contraindicating general anaesthesia or high-frequency low-tidal volume (HFLTV) ventilation, and inability to provide a signed informed consent. All patients who fulfilled the inclusion criteria were consecutively enrolled and randomized to either the study arm (‘QDOT-by-LAWT’) or the control arm (‘CLOSE’) in a 1:1 fashion ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Multidetector computed tomography images were analysed with ADAS 3D™ software (ADAS3D Medical, Barcelona, Spain) to obtain 3D LAWT maps; the 3D LAWT map rendering process was previously described. 8 , 14 Briefly, left atrium (LA) endocardial layer was delineated semi-automatically using a threshold-based segmentation, while the epicardial layer was defined in an automatic way by using an artificial intelligence–based segmentation pipeline integrated into the software, which could be then manually re-adjusted by the user. Finally, LAWT was automatically computed at each point as the distance between each endocardial point and its projection onto the epicardial shell.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation